Determinasi Fasilitas, Kedisiplinan dan Kepemimpinan terhadap Kinerja Karyawan - Mandataris S.Sos.,M.Si (JIAGANIS, 2019)
ABSTRACT     Competitive a company depends on ability of the company to get their optimal performance. Good performance that company haved will be achieved if productivity working of staff that haved progress or imptovement . Many factors can give effect to make good performance staff of a company, include staff themselves or any environment of company. The factors can give determinant  such as facilities, discipline and leadership like in this research. The objective of this research is to know find out facilities, discipline and leadership make significant determination toward staff performance in B`Right PLN Batam. Population of this research is 107 staffs and sample  is 85 staffs.  Method of this research is assosiatif explanatory, that to give  descript the relation between variables of research. Result of the research shown determination coefficient is 0.604, that have meaning 60.4%  of performance affected by facilities, discipline and leadership, the other percent affected by another factors that not investigated in this research. Keywords: Facilities, discipline, leadership, performance